Cylindrical Zwitterionic Particles via Interpolyelectrolyte Complexation on Molecular Polymer Brushes. Issue 8 (16th September 2020) - Pelras, Théophile; Nonappa,; Mahon, Clare S.; Müllner, Markus
Abstract: The fabrication of macromolecular architectures with high aspect ratio and well‐defined internal and external morphologies remains a challenge. The combination of template chemistry and self‐assembly concepts to construct peculiar polymer architectures via a bottom‐up approach is an emerging approach. In this study, a cylindrical template—namely a core–shell molecular polymer brush—and linear diblock copolymers (DBCP) associate to produce high aspect ratio polymer particles via interpolyelectrolyte complexation. Induced, morphological changes are studied using cryogenic transmission electron and atomic force microscopy, while the complexation is further followed by isothermal titration calorimetry and ξ‐potential measurements. Depending on the nature of the complexing DBCP, distinct morphological differences can be achieved. While polymers with a non‐ionic block lead to internal compartmentalization, polymers featuring zwitterionic domains lead to a wrapping of the brush template. Abstract : Interpolyelectrolyte complexation (IPEC) is increasingly used in the bottom‐up fabrication of complex soft matter. Herein, diblock copolymers with a negatively charged and either non‐ionic or zwitterionic block are complexed onto a polycationic molecular polymer brush. The formation of distinct IPEC domains depends on the nature of the charge‐neutral block, resulting in distinct internal compartmentalization or densely charged polyzwitterionic shell.